(untitled) (Bangladesh Journal of Anatomy, 2017)
Background: Identification of sex of an unknown individual from the skeletal remains is the first and the most important step encountered by the forensic experts and archiologists. The distinctive morphology of human skeleton and its clear dimorphism make it of interests from anatomical, obstetrical, radiological and anthropological point of view. The hip bone is considered as an ideal bone for sex determination as it provides the highest accuracy levels. The aim of this study was to collect data regarding morphometric measurements of greater sciatic notch of hip bone and to find out possible variations of greater sciatic notch index in different individuals in relation to sex. Objectives: The cross sectional analytic study was planned to collect data regarding morphometric measurements of greater sciatic notch and also find out possible variations in male and female so that a standard data can be established for future studies in anatomy that can help orthopedic surgeons, radiologists and gynecologists to adopt appropriate plans for diagnosis and treatment. Methods: The study was performed on 180 (one hundred and eighty) dry ossified human left hip bones of unknown sex collected from Department of Anatomy of different Medical College of Dhaka city. The study samples were distributed in male and female sex groups by discriminant function analysis. All the samples were studied morphologically. Measurements of greater sciatic notch were measured with the help of digital slide calipers. Paired students ‘t’test was done for statistical analysis of the result. Results: In the present study the mean width of greater sciatic notch was greater in female than (P<0.001) male. In case of depth of greater sciatic notch significant difference (P<0.01) was found between male and female hip bone. In male, length of posterior segment of greater sciatic notch of hip bone was lower than (P<0.001) female. There was highly significant difference (P<0.001) in the mean of total angle and posterior angle of greater sciatic notch between male and female. The Genoves’ sciatic notch index in male was significantly greater (P<0.001) than female. Bangladesh Journal of Anatomy July 2017, Vol. 15, No. 1, pp. 19-24